THE CONTEMPORARY POLICING CONCEPT: HOW THE GLOBALISATION AFFECTED THE NEW CONCEPT OF INDONESIAN POLICING ON PREDICTIVE POLICING OF “PRESISI” - Jauhar R Sumirat; Satya Dhira A N; Rio Adhikara (Bajang Institute, 2021)
This research is to examine how globalisation affects the concept of policing in Indonesia. The concept of globalisation that affects the development of crime and accelerates the development of the concept of policing to address crime issues is expected to be able to support the transformation of the INP (Indonesia National Police) in combating crimes. The research method used in this study is qualitative. The research technique is library research or literature review which is a research technique that analyses data related to problems, with data collection techniques from literature in the form of books, newspaper magazines and visits to internet sites and other sources that support research. There is a fundamental misconception of the predictive policing concept in most of the INP police member, and there is no specific single bureau that able to manage big data for predictive policing. Predictive policing may not be the ultimate answer for crime prevention. Actual evaluations of the usage of these models in practice lead to mixed results. to aim this, it needed to apply the theory collaborating with the local norms to get the optimal result.